Beyond Neoliberalism and Capital Accumulation Theory: Evidence Learning from Turkey’s Economy - Arif Darmawan; Mehmet Şişman (Universitas Islam Kadiri, 2023)
Neoliberalism is both a body of economic theory and a policy stance. The neoliberal theory claims that a largely unregulated capitalist system (“a free market economy”) embodies the ideal of free individual choice and achieves optimum economic performance. The phase of “embedded liberalism” was succeeded by an era of embedded neoliberalism in which the contradictions of global capitalism were veiled by the hegemonic ideology of individual freedom and prosperity in the nineteenth century. The conditions for a capitalist economy in Turkey were established in the 1920s within the republican political system, which supported the development of national economic capability for capitalist accumulation—albeit with strict government planning of the budget and control over the private sector and foreign trade and investment. After 1980, neoliberal economic reform weakened the statist system and, particularly since 2001, transformed Turkey into a transnational state better suited to the demands of a global economy. This paper tries to identify and find the link between neoliberalism and capital accumulation theory based on learning about Turkey’s economy before and after the crisis. We found that the outcome of neoliberal restructuring experiments depends crucially on pre-existing and changing power structures and relations in the course of state transformations. Thus, Turkey shifted to a neo-liberal model through voluntary choice but as an inevitable and forced outcome of a major balance of payments crisis associated with the exhaustion of the import-substitution model of industrialization.